Unbounded symmetric analytic functions on _1 - Chernega, Iryna; Zagorodnyuk, Andriy (MATHEMATICA SCANDINAVICA, 2018)
We show that each G-analytic symmetric function on an open set of _1 is analytic and construct an example of a symmetric analytic function on _1 which is not of bounded type.